PENGARUH LIKUIDITAS, STRUKTUR MODAL, UKURAN PERUSAHAAN DAN PERTUMBUHAN LABA TERHADAP KUALITAS LABA PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA (BEI) - Ni Made Adi Krisnawati, 11.05.52.0121; Srimindarti, Ceacilia (Students Journal of Accounting and Banking, 2016)
This study examines the effect of liquidity, capital structure, company size and profit growth of the quality of earnings.Â  This research was conducted in the Indonesia stock exchange using analysis unit manufacturing companies that have gone public.The method used in this research is descriptive quantitative method. Sample using purposive sampling techniques and acquired 81 companies in the sample with the study period of 2010 to 2013. The results showed that the size of the companys liquidity and significant effect on the quality of earnings. While the capital structure and profit growth did not significantly affect the quality of earnings. Â Keywords: Liquidity, Capital Structure, Company Size, Growth Income and Earnings Quality